Multi-pass laser welding with cut-wire particles of 50 mm thick steel plates - Mohamed Wahba; Masami Mizutani; Seiji Katayama (Journal of Alloys and Metallurgical Systems)
Multi-pass laser welding with filler wire feeding shows significant potential for welding thick plates. However, this method faces challenges due to the need for edge preparation and stringent control of parameters such as wire feed speed and the relative positioning to the laser beam. Utilizing cut-wire particles instead of solid wire may address these limitations. This investigated the usage of cut-wire particles in multi-pass laser welding of 50 mm thick square groove butt joints. The study involved welding experiments to optimize the amount of cut-wire particles, laser power density, and travel speed for root and buildup passes. The final pass employed hybrid laser-arc welding to compensate for the voids between the cut-wire particles. The joints were successfully welded in eight passes. Mechanical testing demonstrated that the welded joints exhibited strength surpassing that of the base metal. The heat-affected zone displayed a hardness exceeding 350 HV. The fusion zones of the hybrid and buildup passes showed an impact toughness of 100 J, while the root pass fusion zone exhibited an impact toughness of approximately 45 J. This difference was attributed to the presence of a bainitic/martensitic microstructure in the root pass, compared to a mixture of acicular and grain boundary ferrite in the hybrid and buildup passes.